The role of synthetic pesticides in the intensification of highland agriculture in Thailand - Pepijn Schreinemachers (2018)
The objective of this study is to quantify the relationship between synthetic pesticide use and agricultural intensification in the northern highlands of Thailand. We surveyed the crop management decisions of 295 farmers across 12 villages, and assessed the level of pesticide use in terms of monetary value, the active ingredients used, and using the Environmental Impact Quotient method. The results show that 77% of the farmers relied solely on synthetic pesticides for their pest management activities. The average farmer used 13.3 kg of active ingredients per hectare of agricultural land, but the variation was large. The highest levels of pesticide use were observed with the cultivation of cut flowers and greenhouse vegetables, while greater land use intensity was associated with increased usage of synthetic pesticides and a greater potential environmental impact. We found that those farmers following public certification of Good Agricultural Practices (Q-GAP), were neither able to reduce pesticide use nor its environmental impact. The findings suggest that to limit the environmental impact caused by the use of synthetic pesticides, greater priority must be given to developing and promoting non-synthetic methods of pest control together with gradually restricting the supply of highly hazardous pesticides. © 2011 Elsevier Ltd.